Sacrifice and Atonement in Toni Morrison's Beloved and William Faulkner's Light in August - Busch, Austin (Christianity & literature, 2024)
Reading Beloved and Light in August in dialogue with New Testament intertexts and theological traditions of Christian atonement reveals the redemptive logic underlying Sethe’s infanticide and the exorcistic expulsion of Beloved, and the sacrificial logic underlying Joe Christmas’s lynching. Triangulating these and related scenes of racialized violence against models of sacrifice drawn from Girard, Freud, and other theorists discloses the novels’ critique of certain Christian theological interpretations of Jesus’s death that imply the self-perpetuating futility of surrogate sacrifice. This article considers the ideological purposes those assessments play in the historical-cultural contexts the novels imagine and in which they written.